Antimicrobial use: importance of bacterial culture and susceptibility testing. Issue 9 (19th November 2021) - Allerton, Fergus; Nuttall, Tim
Abstract : Background : Tools are needed to assist in the battle against multi‐drug resistant infections. To ensure rational antimicrobial use, it is crucial to identify infectious agents. Aim of the article : This article highlights the application of culture and susceptibility testing, which will assist practitioners in optimising antimicrobial selection. It describes techniques to obtain a representative sample for analysis and how to maximise pathogen viability during transport and handling. Some of the different methodologies employed for bacterial culture and antimicrobial susceptibility testing will be reviewed with guidance on how to interpret the results. We wholeheartedly support practitioner efforts to detect and characterise bacterial pathogens and hope to provide a useful guide to the analysis of these results so that they can inform therapeutic strategy. By working closely with your local veterinary diagnostic laboratory patient care may be enhanced; maintaining open channels of communication with the microbiologist can also provide context to unexpected results. Bacterial culture and susceptibility testing facilitate appropriate antimicrobial selection and, therefore, play a pivotal role in tackling antimicrobial resistance. It is beholden to veterinarians to learn how to use these tools most effectively.